If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6 + -42 = 84 + -8x Reorder the terms: 6 + -42 + 7x = 84 + -8x Combine like terms: 6 + -42 = -36 -36 + 7x = 84 + -8x Solving -36 + 7x = 84 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -36 + 7x + 8x = 84 + -8x + 8x Combine like terms: 7x + 8x = 15x -36 + 15x = 84 + -8x + 8x Combine like terms: -8x + 8x = 0 -36 + 15x = 84 + 0 -36 + 15x = 84 Add '36' to each side of the equation. -36 + 36 + 15x = 84 + 36 Combine like terms: -36 + 36 = 0 0 + 15x = 84 + 36 15x = 84 + 36 Combine like terms: 84 + 36 = 120 15x = 120 Divide each side by '15'. x = 8 Simplifying x = 8
| [-4x]x[-8xyz]= | | (3x-9)=73 | | 2+(n*3)=4*n | | (36p^8)^1/2 | | 2/3x=16-4 | | (4x-5)3=38 | | 5x-12x=3x+15+2x | | 3x+15-6x-10=9x-6-3+5 | | 3x+8=-11+2x | | 0=2x^3-6x^2-32x | | 5p-3pq= | | Y=5/4x-13/x | | 16=4+0.363 | | h+3h+4h=200 | | -5=2-5 | | 100x+33y=21 | | z^2-2z+6=2-i | | 3+6n=6 | | 23*23+b*b=26*26 | | y^2=48y | | 5(6d+1)-3d= | | =(x+4)(x+4)(x+4)x | | 4x^3+3x^2-31x+42=0 | | 2a-2+3=5 | | Cos(35)=x/14 | | Log29/log5 | | (X-5)^2/3=2 | | y=12-2X^2 | | 6=0.1b | | (x+3)(x+3)(x+3)(x-3)x^3= | | Y=-1(-1)+2 | | y=−1/2−5x4 |